THE TERM NATIONAL COLOR, ITS STUDY IN LITERATURE AND ITS SCOPE - Jumayeva Shahlo Shokirovna (Journals Park Publishing, 2023)
The lexicon of a literary work is closely related to the era and the people depicted in it, because the work is a source of information about the history, culture, and customs of the people. In this, the author attaches special importance to the words that express things, concepts and events related to the period he is describing. This is a style that ensures the naturalness of the artistic work and shows the national color.
Keywords: literary work, information about the history, culture, and customs of the people, national color.